(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
This article discusses methodological aspects involved in psychotherapy research, especially the so called process research, that identifies the change processes occurring in the client-therapist’s interaction from a behavior analytic point of view. Brazilian behavior-analytic studies of session analysis illustrate the discussed matters. Issues concerning the categorization of behaviors in clinical interaction, such as the nature of events that compose a group of categories, criteria for reliability and validity of a categorization system, delimitation of the occurrence and registration unit in social interactions and the appropriated measures are discussed. Lastly, different strategies are presented for categorized data systematization, as well as some of the limitations and advantages of each.